2011
DOI: 10.1089/scd.2010.0097
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Stimulation of Tissue Growth Depends on Differentiation State

Abstract: The osteochondral microenvironment involves a complex milieu of cues that facilitate proper tissue development, homeostasis, and repair. This environment is disrupted in disease states such as osteoarthritis. Mesenchymal stem cells (MSCs) are under clinical investigation for the treatment of osteoarthritis given their capacity to differentiate into chondrocytes as well as to secrete a wide array of biologically active factors that support cell proliferation and tissue formation. In fact, the therapeutic action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…From previous findings, we confirmed that OS cells, when cultured with undifferentiated MSCs in a bilayered hydrogel construct, stimulated the chondrogenic differentiation of the latter likely via paracrine effects 24, 30, 3436 . In a parallel study, CG cells, when co-cultured with OS cells, displayed enhanced chondrogenic gene expression for type II collagen and aggrecan as well as increased GAG production in vitro 24 .…”
Section: Discussionsupporting
confidence: 82%
“…From previous findings, we confirmed that OS cells, when cultured with undifferentiated MSCs in a bilayered hydrogel construct, stimulated the chondrogenic differentiation of the latter likely via paracrine effects 24, 30, 3436 . In a parallel study, CG cells, when co-cultured with OS cells, displayed enhanced chondrogenic gene expression for type II collagen and aggrecan as well as increased GAG production in vitro 24 .…”
Section: Discussionsupporting
confidence: 82%
“…Undifferentiated MSC can be used to support angiogenesis in defect sites or modulate immune responses, 21 while treatment strategies that target direct bone repair may benefit from inducing MSC toward the osteoblastic lineage before implantation to promote rapid bone formation and calcium deposition. 22,23 Since MSC exhibit unique secretory and stimulatory characteristics depending on their differentiation state, 4,24 it is important to account for variations in cellular responses to LPA at different degrees of differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Rothenberg et al takes the view that it may not necessarily be the environment we expose the MSC to which determines the type of lineage they differentiate into. It could also be the bioactive factors which the MSC themselves secrete which determine the type of tissue produced [22]. In other words, the MSC may not just act as sources of cells for us to manipulate, but they may themselves be reactant to their microenvironmental conditions, before exposing them to artificial conditions, to allow them to secrete certain factors such as Matrix Metalloproteinase (MMPs) and Transforming Growth Factor 1 (TGF 1) to determine the type of tissue produced.…”
Section: Mscs Of Bone Marrow Originmentioning
confidence: 99%
“…Taking this idea forward, it would therefore be important to consider how we can manipulate the MSC in the predifferentiation state before the MSC has decided which factors it is going to secrete [22] and hence, which subsequent tissue it will produce. This study also proposes that using scaffolds such as gels mixed with MSC can stimulate the MSC in their pre-differentiation state to be more likely to secrete certain factors.…”
Section: Mscs Of Bone Marrow Originmentioning
confidence: 99%
See 1 more Smart Citation